Condition Assessment of Reinforced Concrete Bridges: Current Practice and Research Challenges - Tarek Omar; Moncef L. Nehdi (Infrastructures, 2018)
One quarter of bridges in Canada and the United States need repair. The present study provides a critical overview of the state-of-the-art existing condition assessment techniques for reinforced concrete bridges, with an emphasis on current practice in North America. The techniques were classified into five categories, including visual inspection, load testing, non-destructive evaluation, structural health monitoring, and finite element modelling. The potential applications of these technologies are discussed and compared, highlighting their primary advantages and limitations. The review revealed that quantitative assessment could be effectively achieved using several complementary technologies. It is shown that there is need for concerted research efforts to achieve automated data collection and interpretation analyses. Also, the configuration of monitoring systems was found to be paramount in effectively assessing bridge performance parameters of interest. The study suggests appropriate investigation methods for some bridge deterioration mechanisms. Knowledge gaps and challenges in this field are outlined in order to motivate further research and development of these technologies.